The husband as a labor companion has a good influence on the duration of labor - Gita Nirmala Sari; Shella Oktavia; Aticeh Aticeh; Eprila Eprila; Li Yuting (Journal of Health Technology Assessment in Midwifery, 2023)
Birth support can prevent prolonged labor. The husband can carry out this support as a delivery companion. This study aims to assess the effect of the husband's role as a labor companion on the duration of labor. This research is an observational analytic study with a cross-sectional design. The samples in this study were 60 pairs of mothers and their husbands who met the inclusion and exclusion criteria. Data were obtained using the observation sheet on the husband's role and partograph. The analysis used in this study was the chi-square test and logistic regression. Mothers in labor will have an increased risk of 2.85 to experience a prolonged first stage of labor if the husband does not provide sufficient support as a birth companion during labor (OR=2.8, 95% CI=1.52-5.16). Good labor companion by the husband will be able to prevent mothers from experiencing a long second stage of labor (OR = 0.34, 95% CI = 0.18-0.62). The role of a good husband as a birth companion is to maintain the expected time for the first and second stages of labor and prevent the long duration of labor.